United Kingdom radiation oncology - past, present and future. - Jones, B (2009)
The United Kingdom Radiation Oncology (UKRO) conference was formed as a result of discussions held in the early 1990s and the first meeting was held in York in 2001. Cardiff, Wales, was the setting of the fifth UKRO conference during April 2009. These meetings have allowed all the sub-disciplines of radiation oncology to meet over 3 days in order to provide education on most technical aspects of modern radiotherapy, with key invited speakers from abroad. The UK and other countries face considerable dilemmas as to how best to implement new treatment techniques, including particle therapy, in a state-funded health service.